Genetic and epigenetic studies of amyotrophic lateral sclerosis. Issue 1 (May 2013) - Al-Chalabi, Ammar; Kwak, Shin; Mehler, Mark; Rouleau, Guy; Siddique, Teepu; Strong, Michael; Leigh, Peter Nigel
Abstract The identification of genetic and epigenetic factors that are associated with an increased risk of developing amyotrophic lateral sclerosis (ALS), or that modify the age of onset or rate of progression, requires a multimodal research strategy, facilitated through international collaboration. The discovery of several ALS genes strongly linked to RNA biology, the proteasome pathway, and axonal transport suggest they have an important role in pathogenesis, but the immense complexity of these processes is also apparent. The increasing rate of genetic discoveries brings the hope of designing more targeted and efficacious therapies.